THE EFFECT OF KATUK (Sauropus androgynus L. Merr) ETHANOL EXTRACT ON OVARIAN MATURITY OF MUD CRAB (Scylla sp) - Awaludin, Awaludin (Jurnal Borneo Saintek, 2020)
Katuk leaves are plants that contain sterols. Sterols are steroid precursors used for the development of mud crab ovaries. This study aims to determine the development of mangrove crab ovaries by giving katuk leaf extract. Stages of research include katuk leaf extraction, experiments by injecting the mother crab consisting of 3 treatments consisting of treatment A (control), treatment B (0.25 mg / g body weight), treatment C (0.5 mg / g body weight) ) maintained for 20 days by feeding trash fish and measuring parameters including morphological ovarian development, gonad somatic index, and hepatosomatic index. The results of the study on C treatment on the 20th day of observation by ovarian morphology have developed in the TKO IV phase, the final B TKO III treatment and the A-phase TKO III treatment. GSI on the 20th day in treatment C showed the highest GSI value of 16.1% and the lowest in treatment A was 12.2%. It can be concluded that the administration of katuk extract can accelerate the ovarian maturity of mud crabs.